A Comprehensive Analysis of Poverty in India - Panagariya, Arvind; Mukim, Megha (World Bank, Washington, DC, 2014)
This paper offers a comprehensive analysis of poverty in India. It shows that no matter which of the two official poverty lines is used, poverty has declined steadily in all states and for all social and religious groups. Accelerated growth between fiscal years 2004-2005 and 2009-2010 led to an accelerated decline in poverty rates. Moreover, the decline in poverty rates during these years was sharper for the socially disadvantaged groups relative to upper caste groups, so that a narrowing of the gap in the poverty rates is observed between the two sets of social groups. The paper also provides a discussion of the recent controversies in India regarding the choice of poverty lines.